Successful integration of practical Cisco CCNA in the Computer Networks Design course - Spasov, Dejan; Ristov, Sashko; Gushev, Marjan (IEEE, 2015)
This paper presents a new curriculum for the Computer Networks Design course intended as advanced course for computer science students. We have developed an adaptive curriculum, which introduces two CISCO CCNA 3 (LAN Switching) and 4 (WAN Technologies) courses instead of the existing (regular) tutorials and laboratory exercises. The students can choose whether they would like to learn the course by a more practical approach using the CISCO CCNA integration, rather than by a more theoretical approach. The evaluation show much better results for the students that follow the course using the integration of the CISCO practical exercises, rather than those that follow the course regularly only by theoretical approach.
Keywords: Curriculum; Education; Cisco; CCNA; Teaching methods